PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN CV. PONDOK LEBAH WILAYAH JABODETABEK - Eko Saputro; Arief Syah Safrianto (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
The analyze the effect of service quality and product quality on consumer satisfaction CV. Pondok Lebah Wilayah Jabodetabek. This research is included in the category of causal associative research using a quantitative approach. The research population is all consumers of CV. Pondok Lebah Wilayah Jabodetabek. The sampling technique used was purposive sampling. The research method using simultaneous and partially linear regression analysis. The results of the study show that both service quality and product quality have a positive and significant effect on consumer satisfaction of CV. Pondok Lebah Wilayah Jabodetabek.